Four persons , , , and have a total sum of . They play a game of cyclic transfer. goes first, and gives of what he has to . Next, gives of his new amount to . Next gives of his new amount to player , and finally, gives of his new amount to player . At the end of all this, the four players check the amounts they have. They find that players and have switched their initial amounts, while players and ended up with the same amounts they started with. What was the amount that player had initially?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let the amounts the four players have initially and after the game be a 0 , b 0 , c 0 , and d 0 ; and a 1 , b 1 , c 1 , and d 1 respectively. Then a 0 + b 0 + c 0 + d 0 = 1 4 6 0 and
⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ b 1 c 1 d 1 a 1 = 0 . 8 ( 0 . 2 a 0 + b 0 ) = 0 . 8 ( 0 . 0 4 a 0 + 0 . 2 b 0 + c 0 ) = 0 . 8 ( 0 . 0 0 8 a 0 + 0 . 0 4 b 0 + 0 . 2 c 0 + d 0 ) = 0 . 8 a 0 + 0 . 2 ( 0 . 0 0 8 a 0 + 0 . 0 4 b 0 + 0 . 2 c 0 + d 0 )
Since
a 1 = d 0 d 1 = a 0 b 1 = c 1 ( 1 ) + ( 2 ) : ⟹ 0 . 8 0 1 6 a 0 + 0 . 0 0 8 b 0 + 0 . 0 4 c 0 − 0 . 8 d 0 = 0 ⟹ − 0 . 9 9 3 6 a 0 + 0 . 0 3 2 b 0 + 0 . 1 6 c 0 + 0 . 8 d 0 = 0 ⟹ − 0 . 1 2 8 a 0 − 0 . 6 4 b 0 + 0 . 8 c 0 = 0 ⟹ − 0 . 1 9 2 a 0 + 0 . 0 4 b 0 + 0 . 2 c 0 = 0 . . . ( 1 ) . . . ( 2 ) . . . ( 3 ) . . . ( 4 )
( 3 ) − 4 × ( 4 ) : ( 3 ) + 1 6 × ( 4 ) : ( 1 ) : 0 . 6 4 a 0 − 0 . 8 b 0 = 0 − 0 . 3 2 a 0 + 4 b 0 = 0 0 . 8 4 a 0 − 0 . 8 d 0 = 0 ⟹ b 0 = 0 . 8 a 0 ⟹ c 0 = 0 . 8 a 0 ⟹ d 0 = 1 . 0 5 a 0
Therefore, a 0 + b 0 + c 0 + d 0 = 3 . 6 5 a 0 = 1 4 6 0 ⟹ a 0 = 4 0 0 ⟹ b 0 = 0 . 8 a 0 = 3 2 0 .